2020
DOI: 10.1002/lt.25783
|View full text |Cite
|
Sign up to set email alerts
|

Debate on Selection Criteria for Liver Transplantation for Alcoholic Hepatitis: Tighten or Loosen?

Abstract: Although liver transplantation (LT) for alcohol‐associated liver disease (ALD) is a well‐accepted practice, LT for severe alcoholic hepatitis (AH) remains controversial due to concerns about the limited organ supply and the risk of return to harmful drinking. Recognizing an increasing body of favorable evidence, a convergence of practice guideline recommendations from leading hepatology and gastroenterology societies have suggested that the length of abstinence should not be a sole criterion for LT selection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, the assessment period pre‐LT for those with end‐stage alcoholic liver disease raises difficult questions. Usually, a period of abstinence lasting 6 months or longer is required for someone to be eligible for LT, although these criteria remain a topic of debate (Im & Neuberger, 2020; Syed et al., 2020). Multiple studies have indicated that alcohol liver disease patients experience poor outcomes post‐LT if they continue consuming alcohol (Cuadrado et al., 2005; DiMartini et al., 2006; Pfitzmann et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the assessment period pre‐LT for those with end‐stage alcoholic liver disease raises difficult questions. Usually, a period of abstinence lasting 6 months or longer is required for someone to be eligible for LT, although these criteria remain a topic of debate (Im & Neuberger, 2020; Syed et al., 2020). Multiple studies have indicated that alcohol liver disease patients experience poor outcomes post‐LT if they continue consuming alcohol (Cuadrado et al., 2005; DiMartini et al., 2006; Pfitzmann et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This arbitrary threshold of abstinence is controversial and is not a strong predicator of relapse reduction 32,33 . Early LT performed for carefully selected severe alcoholic hepatitis (SAH) patients with favorable psychosocial and clinical profile without 6 months of abstinence was shown to have lower rates of harmful alcohol relapse post LT without any reduction in post‐LT survival 34–37 . In fact, a recent meta‐analysis of patients who underwent LT for SAH has revealed an alcohol relapse rate of 14%, similar to those undergoing elective LT for alcohol‐related cirrhosis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…This also highlights that LT does not cure AUD, which requires ongoing monitoring and treatment. LT for severe alcohol-associated hepatitis (and even AAC) is an evolving field, and whether to tighten or loosen transplant selection criteria remains a topic of debate [ 117 ].…”
Section: Liver Transplantationmentioning
confidence: 99%